An Analysis of a Red-Light Camera Program in the City of Milwaukee - Regan, Molly; Moran, Christian; Kriz, Karyn (My University, 2006)
Red-light running is the cause of approximately 1,340 crashes each year in the City of Milwaukee, resulting in an estimated societal cost of $131 million per year. This report analyzes whether implementing a red-light camera system at dangerous intersections would increase safety and create additional revenue opportunities for the city. The authors find that placing cameras at the city's 13 most dangerous intersections would result in a net present benefit of $7.6 million and create additional revenue of $4.8 million during a five-year period of time. Therefore, the authors recommend the City of Milwaukee implement a red-light camera program.
For PA 869: Public Affairs Workshop, Domestic Issues